The socioeconomic consequences of population ageing: aspects of modern challenges in the Russian Federation - G. Mabiala; I. A. Sukhareva; D. V. Linskiy; E. V. Trusevich; E. E. Shamilevа (Модернизация, инновация, развитие, 2023)
Purpose: the article summarizes the key characteristics of the population ageing phenomenon and identifies the channels through which it has an impact on the demographic crisis parameters as well as the socioeconomic growth of the country.Methods: the study is based on tracking the consequences associated with the phenomenon of population ageing. Simultaneously, computational and graphical methods, comparative and retrospective analysis of the sex and age pyramids, expert and empirical assessment of the trends in the structure of the population older than 60-65 years, as well as its economic burden per 1,000 able-bodied people, were used.Results: the main parameters of the socioeconomic impacts of population ageing are determined. Age limits and essential features of this phenomenon are revealed. The forecast trend of socioeconomic parameters of population ageing is supported by the SWOT analysis matrix, and a conceptual model for the implementation of systematic adjustment measures for the ongoing demographic crisis is proposed.Conclusions and Relevance: the article demonstrates that population ageing is not a fundamental socioeconomic problem that endangers the well-being of the population over working age. However, it has many negative consequences for the socioeconomic growth of the country that are still being researched; the real threats come not from population ageing as such, but from the existing disproportion in the workload of the population over 60-65 years old per 1,000 able-bodied population. Despite the relative parameters of the ageing trend in Russia, in the future, the life expectancy of the population will be 73.58-75.03 years.